The influence of strain on the Verwey transition as a function of dopant concentration: towards a geobarometer for magnetite-bearing rocks. Issue 1 (12th June 2019) - Biało, Izabela; Kozłowski, Andrzej; Wack, Michael; Włodek, Adam; Gondek, Łukasz; Kąkol, Zbigniew; Hochleitner, Rupert; Żywczak, Antoni; Chlan, Vojtech; Gilder, Stuart A
SUMMARY: Magnetite is an abundant magnetic mineral that commonly records the ancient magnetic field in a wide variety of rock types. When cooled below ≈124 K, magnetite undergoes a phase transition, called the Verwey transition, whose characteristics are highly sensitive to grain size and stoichiometry. Studying the Verwey transition thus yields information on the formation conditions and compositions of rocks. The transition is also stress sensitive, thereby opening an avenue to understanding a rock's strain history; however, the reason for the stress sensitivity is poorly understood. In particular, the temperature of the transition decreases when measured under pressure, yet mostly increases upon pressure release. Moreover, the stress sensitivity of the transition as a function of dopant concentration, especially after pressure cycling, was never systematically tested. We addressed these issues in order to further develop magnetite as a pressure gauge. Multidomain magnetite samples were pressure cycled up to maximum pressures of ∼5 GPa at room temperature to measure the influence of strain on the Verwey transition temperature as a function of dopant concentration after full decompression. The transition temperature measured via changes in magnetic remanence ($T_{\rm V}^{M}$ ) systematically increased with respect to pressure ( P ) in more doped samples, where domain wall pinning from impurities dominates $\mathrm{d}T_{\rm V} ^{\rm M}/\mathrm{d}P$ . In less doped samples, no to only moderate pressure cycling dependence on $T_{\rm V}^{\rm M}$ was observed. Bulk coercive force ( B c ) and magnetic remanence after saturation ( M rs ) measured above or below the transition also increased with respect to pressure, but here effects related to permanent strain of the lattice structure prevail, and B c versus P is steeper for less doped samples. B c versus P increases in all cases, with a difference in slope dictated by dopant concentrations segregating the first to second-order nature of the transition. Thus, strain developed during pressure cycling controls $T_{\rm V}^{\rm M}$ and coercivity by a mechanism based on pinning of magnetic domains by both interstitial cations and structural lattice distortions. The combined observables, $T_{\rm V}^{\rm M}$ and B c − M rs, reflect both the dopant level and strain state of magnetite, which can quantify the pressure multidomain magnetite has experienced, especially in the range between 1 and 5 GPa. Based on these new results, we present a model that distinguishes between electronic versus defect-driven processes explaining the strain-related influences on the transition. Magnetite's use as a geobarometer is thus a measure of its defect state, which is expressed through two somewhat independent mechanisms when sensed by magnetic observations.